Thinking about computational thinking: Origins of computational thinking in educational computing. Issue 1 (2nd January 2020) - Bull, Glen; Garofalo, Joe; Hguyen, N. Rich
Abstract: An educational team founded by Seymour Papert at MIT has developed an evolving series of computing environments designed to facilitate computational thinking. Papert outlined the goal of developing educational environments to facilitate the use of computer as a computational object in a seminal publication, Teaching Children Thinking (1970). He subsequently introduced the term Computational Thinking in Mindstorms: Children, Computers, and Powerful Ideas (1980). The understanding gained through five decades of research provides an important context for contemporary efforts to integrate computational thinking in schools.